Assessment of dental anxiety among the patients visiting a dental institution: a cross-sectional, questionnaire-based survey - Sapna, Balachandrareddy; Tumminkatti, Afraa Nazish A.; Kousar, Afreen; Tumminkatte, Aaliyah T.; Bhavana, Dontireddy; Sulthana, D. S. Gazala; Kavya , Kadaramandagi M. (International Journal Of Community Medicine And Public Health, 2025)
Background: This study aimed to assess dental anxiety among patients visiting a dental institution in Davangere, India. Methods: This study included 400 participants aged ≥18 years. Demographic and non-demographic information were obtained through a questionnaire. Dental anxiety levels were determined using a language-translated version (Kannada) of the Modified Dental Anxiety Scale (MDAS-K). Statistical analyses were performed using the Mann–Whitney U test, Kruskal–Wallis ANOVA, and Chi-square tests. Results: The mean overall dental anxiety score for 227 female and 173 male participants, aged between 18 and 82 years was 16.6±2.6. The Anxiety score was slightly higher among Females, younger and early adults, and highly educated patients with lower incomes. However, this difference was not statistically significant. First-time visitors, those who had unpleasant dental experiences in the past (p=0.001), those who avoided dental treatment because of anxiety (p=0.000), and those who graded their oral health as poor to average (p=0.006), all had slightly higher mean anxiety scores. The degree of dental anxiety did not significantly correlate with any of the demographic or non-demographic factors (p>0.05). Conclusion: The level of dental anxiety was found to be high (62.8%) and extremely high (22.5%) among the patients who visited a dental institution in Davangere City.